2021
DOI: 10.1038/s41598-021-86647-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory properties of Chinese Herbal Formula SanHuang decoction on biofilm formation by antibiotic-resistant Staphylococcal strains

Abstract: The aim of this study was to explore the effect of Chinese herbal SanHuang decoction (SH) on biofilm formation of antibiotic-resistant Staphylococci on titanium surface, and to explore its mechanism. Biofilm-forming ATCC 35984, ATCC 43300 and MRSE 287 were used in this study. The MICs of SH and vancomycin against Staphylococci were determined by the broth microdilution method. Six groups were designed, namely control group (bacteria cultured with medium), 1/8MIC SH group (1MIC SH was diluted by 1/8 using TSB o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…WTG is characterized by dispelling wind, dredging meridians, tonifying qi, and activating blood circulation, thereby benefiting tendon relaxation, collateral activation, blood stasis elimination, and pain relief. As a characteristic external therapy, the external application of TCM can effectively regulate the body balance by local drug penetration to dispel nearby evil and treat internal disorder via an external application [34]. Previous studies have reported that multiple Chinese herbal medicines and extracts in WTG formula produce vital effects on pain improvement in RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…WTG is characterized by dispelling wind, dredging meridians, tonifying qi, and activating blood circulation, thereby benefiting tendon relaxation, collateral activation, blood stasis elimination, and pain relief. As a characteristic external therapy, the external application of TCM can effectively regulate the body balance by local drug penetration to dispel nearby evil and treat internal disorder via an external application [34]. Previous studies have reported that multiple Chinese herbal medicines and extracts in WTG formula produce vital effects on pain improvement in RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…In this study a positive correlation between glucose concentration and biofilm formation was shown ( Croes et al., 2009 ). In addition, a correlation between a methicillin-resistance and the biofilm formation has been shown ( Zhang et al., 2021 ). In this study, S. epidermidis ATCC 35984 is the only methicillin-resistant strain used in our experimental setting.…”
Section: Discussionmentioning
confidence: 99%
“…• C. The precipitated DNA was washed with 70% ethanol and resuspended in 100 µl of Milli-Q water. PCR amplification of 16srRNA and nuc genes was done(Abbasi-Montazeri et al, 2013;Zhang et al, 2021; Supplementary Table1). The confirmed isolates were then stored at −70 • C in brain heart infusion (BHI) broth with 30% glycerol.…”
mentioning
confidence: 99%